When the workshop is working: The role of artists in collaborative research with young people and communities. (9th November 2015) - Graham, Helen; Hill, Katie; Holland, Tessa; Pool, Steve
Abstract : Purpose: – This paper comes from workshop activities and structured reflection by a group of artists and researchers who have been using artistic practice within research projects aimed at enabling researchers to collaborate with communities. The paper aims to discuss these issues. Design/methodology/approach: – Three out of four in the group have a practicing creative background and their own studio/workshop space. Findings: – Artists are often employed – whether in schools or research projects – to run workshops; to bring a distinctive set of skills that enable learning or collaboration to take place. In this paper the authors reflect on the different meanings and connotations of "workshop" – as noun (as a place where certain types of activity happen, a bounded space) and a verb (to work something through; to make something together). From there the authors will then draw out the different principles of what artistic practice can offer towards creating a collaborative space for new knowledge to emerge. Research limitations/implications: – Key ideas include different repertories of structuring to enable different forms of social interaction; the role of materal/ality and body in shifting what can be recognised as knowing; and the skills of "thinking on your feet", being responsive and improvising. Originality/value: – The authors will conclude by reflecting on aspects to consider when developing workshops as part of collaborative research projects.